Інкапсулювання наночастинок AgI кремнеземом - Mudrak, I. M.; Storozhuk, L. P.; Gorbyk, P. P.; Gunya, G. M.; Danylenko, M. I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2018)
Technique for silica encapsulation AgI nanoparticles was studied, which based on Stober method. Optimal reagents ratio was established for obtaining AgI nanoparticles coated in silica shell. Formation onto AgI surface quasi-regularly shaped silica shell was proved by transmission electron microcopy, UV - visible and IR-spectroscopy.